Total carbon and nitrogen, and δ13C in sediment core SF-07 obtained along the coastal plain of Babitonga Bay-Santa Catarina-Brazil - Cohen, Marcelo Cancela Lisboa; Fontes, Neuza; Rodrigues, Érika do Socorro Ferreira; Pessenda, Luiz C R; França, Marlon; Garret, Ed; Ryu, Junghyung (In: Cohen, MCL et al. (2025): Topographic, vegetation, radiocarbon and stratigraphic data from Babitonga Bay-Santa Catarina-Brazil [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.985002, 2025)
Fieldwork was conducted in August 2017 to sample sediment cores. The sediments were treated with 4% hydrochloric acid (HCl) to remove carbonates, then washed with distilled water until the pH reached 6. They were subsequently dried at 50°C and homogenized. The samples were analyzed for total organic carbon (TOC) and total nitrogen (TN) at the Stable Isotope Laboratory of CENA/USP. Results were expressed as a percentage of dry weight, with analytical precision of 0.09% for TOC and 0.07% for TN. The δ13C values were reported in per mille (‰) relative to VPDB, with a precision of 0.2‰.
Keywords: isotopes; mangrove; radiocarbon age; South Brazil